EVALUASI PROGRAM PENCEGAHAN STUNTING LINTAS SEKTOR - Widya Kaharani Putri; Sudrajah Warajati Kisnawaty; Nurul Fatimah; Anindita Hasniati (Jurnal Kesehatan, 2023)
The high prevalence of stunting in Indonesia has become a pressing issue that needs to be addressed. Stunting is a health disorder caused by malnutrition, and its consequences include suboptimal intelligence, increased susceptibility to diseases, and the risk of reduced productivity, which can hinder economic growth and exacerbate poverty. The objective of this research is to describe the evaluation of a cross-sectoral stunting prevention program in the Margomulyo village using a qualitative descriptive method. The components evaluated in this study include funding, human resources, supplementary feeding (PMT), and counseling. The implementation has involved various sectors such as the village government, the Village Family Welfare Empowerment Group (PKK), the local health center (Puskesmas), and the community, all working in synergy to ensure the success of the stunting prevention program in Margomulyo village.Keywords: Evaluation, Stunting Program